E-144 Treatment of wide-necked bifurcation aneurysms with the eclips device: five year experience of a single center. (23rd July 2022) - Diestro, J; Keough, M; Ashforth, R; Chow, M; Rempel, J; Marotta, T; O'Kelly, C
Abstract : Background and Purpose: The endovascular clip system (eCLIPs) is a novel device with both neck bridging and flow diversion properties that make it suitable for the treatment of wide-necked bifurcation aneurysms. We aim to describe the clinical and radiologic outcomes of the eCLIPs device, including the first-in-man use of the latest version of the device. Materials and Methods: This is a retrospective case series on all the wide-necked bifurcation aneurysms treated with the eCLIPs device in our center. The immediate and latest radiologic and clinical outcomes were assessed. Results: The device was successfully implanted in 12 out of 13 patients. After a median follow-up period of 19 months (Range: 3 months- 64 months), all patients with available data (11/12) had a good radiologic outcome (Modified Raymond-Roy Classification scores of 1 or 2). Two patients (18.1%) underwent retreatment with simple coiling through the device. One of these had a subarachnoid hemorrhage prior to retreatment. There were no major complications (death or permanent neurologic deficits) associated with the use of the device. Conclusion: Our series demonstrates occlusion rates that are similar to standard stent-assisted coiling and intrasaccular flow diversion for wide-necked bifurcation aneurysms. Larger registry-based studies are necessary to support our findings. Disclosures: J. Diestro: 6; C; Medtronic Honorarium. M. Keough: None. R. Ashforth: None. M. Chow: None. J. Rempel: None. T. Marotta: 4; C; Evasc Medical Systems. C. O'Kelly: None.